Correlations and Path Analysis of Yield Traits in Sorghum Grown in Southwestern Highlands of Uganda - Akatwijuka, R.; Rubaihayo, P.R.; Odong, T.L. (African Crop Science Journal, 2019)
The study of relationships among traits is essential for assessing the feasibility of joint selection for two or more traits. Path coefficient analysis partitions correlation coefficient into direct and indirect contributions of various traits towards dependent variable, thus guiding effective selection. A study was conducted to determine the correlation and path coefficients for sorghum (Sorghum bicolor L. Moench) grain yield and quantitative traits among 47 sorghum cultivars collected from southwestern highlands of Uganda. The study was conducted at Kachwekano Research Farm in Kabale District in southwestern Uganda, at an altitude of 2,223 metres above sea level, during the two successive sorghum growing seasons of December 2014 to August 2015 and December 2015 to August 2016. Correlations revealed strong significant trait associations (P<0.001) for grain yield with panicle weight (r=0.938), and moderately strong relationships with panicle width (r=0.619), stem girth (r= 0.674), and leaf width (r=0.576). Grain yield revealed a non-significant negative correlation with days to 50% flowering (r=-0.011). Regression analysis revealed that panicle weight and plant height had the highest direct effect on grain yield of 1.085 and 0.2097, respectively. Path coefficient analysis revealed that stem girth (0.814), leaf width (0.74901) and panicle width (0.713) had the highest indirect contributions to grain yield. The residual effect was low (R=0.11), with high adjusted R2 value (0.89).
Keywords: Path coefficients; regression; Sorghum bicolor